2022
DOI: 10.1186/s12916-022-02427-9
|View full text |Cite
|
Sign up to set email alerts
|

Costs of multimorbidity: a systematic review and meta-analyses

Abstract: Background Multimorbidity is a rising global phenomenon, placing strains on countries’ population health and finances. This systematic review provides insight into the costs of multimorbidity through addressing the following primary and secondary research questions: What evidence exists on the costs of multimorbidity? How do costs of specific disease combinations vary across countries? How do multimorbidity costs vary across disease combinations? What “cost ingredients” are most commonly includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 121 publications
(121 reference statements)
0
40
1
Order By: Relevance
“…When we consider the total spending associated with combinations (i.e., including the coefficients of the intercept, covariates, single conditions, and three dyads in the case of triads), the top five highest spending with observed prevalence greater than 50 per 100,000 were combinations of EMBI disorders + anemias + skin and subcutaneous diseases ($7,120 [6,899,7,319]), chronic kidney disease + EMBI disorders ($6,730 [6,387,7,29]), EMBI disorders + anemias + hypertension ($6,325 [5,762,6,950]), cirrhosis + EMBI disorders ($5,370 [5,236,5,528]), ischemic heart disease (IHD)-related conditions + hypertension + hyperlipidemia ($5,339 [5,115,5,574]). Note that while these have the highest estimated spending, they do not have the highest observed prevalence.…”
Section: Plos Medicinementioning
confidence: 99%
See 2 more Smart Citations
“…When we consider the total spending associated with combinations (i.e., including the coefficients of the intercept, covariates, single conditions, and three dyads in the case of triads), the top five highest spending with observed prevalence greater than 50 per 100,000 were combinations of EMBI disorders + anemias + skin and subcutaneous diseases ($7,120 [6,899,7,319]), chronic kidney disease + EMBI disorders ($6,730 [6,387,7,29]), EMBI disorders + anemias + hypertension ($6,325 [5,762,6,950]), cirrhosis + EMBI disorders ($5,370 [5,236,5,528]), ischemic heart disease (IHD)-related conditions + hypertension + hyperlipidemia ($5,339 [5,115,5,574]). Note that while these have the highest estimated spending, they do not have the highest observed prevalence.…”
Section: Plos Medicinementioning
confidence: 99%
“…With the rise in multimorbidity, however, it has become more difficult to accurately associate spending to single conditions. Upon reviewing previous literature of similar inquiries and recent systematic reviews on the cost of multimorbidity, we identified four main gaps in estimating spending in the context of multimorbidity [7,8]. First, most studies apply a simple definition of multimorbidity, commonly the count of conditions an individual has in addition to a base condition, and do not consider which additional diseases are being bundled [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review highlighted a paucity of multimorbidity costing studies from low-income and middle-income countries (LMICs). 2 When describing global patterns of multimorbidity, Afshar et al reported a positive but non-linear association between country GDP and multimorbidity prevalence, and also identified an inverse association between multimorbidity and socioeconomic status (SES) in countries with the highest GDP, with the gradient sometimes reversed in countries with lower GDP. 3 Understanding the social and structural forces that drive the clustering of diseases, thereby exacerbating…”
Section: Introductionmentioning
confidence: 99%
“…It affects all ages, but burden is highest among older adults and is associated with increased mortality2 and reduced health-related quality of life 3 4. People living with multimorbidity also have functional impairment,5 higher healthcare utilisation but less continuity of care6 and pose a significant economic burden to families, health systems and society 7–10…”
Section: Introductionmentioning
confidence: 99%